2015
DOI: 10.1002/aic.14895
|View full text |Cite
|
Sign up to set email alerts
|

On the leakage flow around gas bubbles in slug flow in a microchannel

Abstract: The leakage flow is that liquid does not push gas bubbles and leaks through the channel corners. This leakage flow was confirmed by tracking particles moving in the liquid film with a double light path method and was quantified by tracking the gas-liquid interface movement. The results show that leakage flow varies during bubble formation process. The average net leakage flow Q net-leak in a bubble formation cycle at T-junction can be as large as 62.4% of the feeding liquid flow rate, depending on the liquid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Falconi et al reported detailed velocity distribution in the film through three numerical methods and showed a local back flow region in the rear part of the liquid film for a regular slug flow. Although there are several studies that support significant leakage flow, it was not directly observed . Or more accurately, a complete route of leakage flow overtaking a bubble/droplet was not directly observed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Falconi et al reported detailed velocity distribution in the film through three numerical methods and showed a local back flow region in the rear part of the liquid film for a regular slug flow. Although there are several studies that support significant leakage flow, it was not directly observed . Or more accurately, a complete route of leakage flow overtaking a bubble/droplet was not directly observed.…”
Section: Introductionmentioning
confidence: 96%
“…Different from most studies in literature, the present work focuses on the leakage flow which largely impacts the flow hydrodynamics and is still an important problem remaining unsolved . In rectangular channels, as bubbles/droplets cannot fill the corners, significant amount of liquid flows through the corners and bypasses them, leading to leakage flow.…”
Section: Introductionmentioning
confidence: 99%
“…For the solving of the coupled equations, the mass transfer coefficient, the specific surface area, and Q f need to be defined. Q f is a problem unsolved for slug flow in microchannels, especially in rectangular channels . In this work, Q f is approximated by treating the channel cross‐section to be circular, similar to the treatment of Ładosz and Rudolf von Rohr .…”
Section: Resultsmentioning
confidence: 99%
“…Q f is a problem unsolved for slug flow in microchannels, especially in rectangular channels. [49][50][51] In this work, Q f is approximated by treating the channel cross-section to be circular, similar to the treatment of Ładosz and Rudolf von Rohr. 52 In this way, Q f can be obtained by integrating the liquid velocity profile in the slug, which is assumed to conform to the Poiseuille flow:…”
Section: Modeling Of Mass Transfermentioning
confidence: 99%
“…In rectangular channels, the film has a different thickness along the angular coordinate [39,[71][72][73]. Also a significant amount of liquid can move in the back flow at the corners of the channel [74][75][76]. To find the flux of a continuous phase through a film, integration over the angular coordinate is necessary.…”
Section: Methods For Calculating Slug-flow Hydrodynamics At High-pressmentioning
confidence: 99%